Biological control of Cercospora leaf spot disease of sugar beet using Bacillus subtilis - Heba-Alla AbdElfatah; Hadeel M. M. Khalil Bagy; Mohamed S. Mohamed; Mennatallah M. A. El-Geddawy; Rofida F. Moftah; Nashwa M. A. Sallam (Egyptian Journal of Biological Pest Control)
Abstract Background This study examines the application of safe and sustainable management methods for Cercospora leaf spot disease, with a focus on endophytic bacteria such as Bacillus subtilis. These beneficial bacteria can effectively reduce Cercospora leaf spot disease (CLS) severity while enhancing crop production and improving the sugar content of sugar beet roots. Results From naturally infected sugar beet plants, 23 fungal isolates were obtained. Pathogenicity tests on sugar beet (cv. Hossam) were conducted under greenhouse conditions. All isolates were pathogenic to sugar beet, with significant variations in virulence among them. The highest pathogenic isolate was No. 21 with a percentage of 87.65%. This isolate was characterized using ITS1 and ITS4 primers as Cercospora beticola (C. beticola). Using endophytic bacteria to enhance disease resistance is a promising and environmentally friendly approach to controlling crop plant diseases. This study focused on isolating twenty-five endophytic bacteria from different parts of healthy sugar beet plants. These isolates were tested against C. beticola in vitro. The most successful isolate in suppressing the pathogen growth was No. 15. The antagonistic isolate was identified using 16 s-rDNA sequencing as Bacillus subtilis. The effectiveness of B. subtilis in managing Cercospora leaf spot disease in sugar beet was assessed under greenhouse conditions. Plants treated with B. subtilis exhibited the lowest disease severity compared to the infected plants (control disease). The application of B. subtilis led to a significant reduction in reducing sugar content (0.94 g/l) and a marked increase in sucrose concentration, reaching 17.36%, compared to the control disease (1.23 g/l and 10.18%, respectively). Under field conditions, bacteria had a comparable impact on disease severity as exhibited in the greenhouse. Additionally, it contributed to an increase in crop yield. Conclusion B. subtilis could be a promising candidate for the sustainable management of Cercospora leaf spot disease in sugar beet.